2010
DOI: 10.1124/jpet.110.165852
|View full text |Cite
|
Sign up to set email alerts
|

Sulindac and Its Metabolites Inhibit Multiple Transport Proteins in Rat and Human Hepatocytes

Abstract: Sulindac is a commonly used nonsteroidal anti-inflammatory drug. This study tested the hypothesis that sulindac-mediated drug-drug interactions and/or hepatotoxicity may be caused, in part, by inhibition of proteins responsible for the hepatic transport of drugs and/or bile acids by sulindac and/or sulindac metabolites [sulindac sulfone (S-sulfone) and sulindac sulfide (S-sulfide)]. The uptake and excretion of model substrates, [3 H]estradiol 17-␤-glucuronide (E217G), and nitrofurantoin (NF), were investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…To date, knowledge about the uptake of NSAIDs from blood into hepatocytes is limited. It has been demonstrated in rats that the uptake transporter Oat2 (Slc22a7) is involved in the hepatic uptake of ketoprofen (Morita et al, 2005), and recently it has been shown that sulindac and its metabolites inhibited multiple transport proteins in primary rat and human hepatocytes as tested with model substrates, e.g., taurocholate and estradiol-17␤-glucuronide (Lee et al, 2010). To date, the molecular mechanisms of NSAID uptake into hepatocytes are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To date, knowledge about the uptake of NSAIDs from blood into hepatocytes is limited. It has been demonstrated in rats that the uptake transporter Oat2 (Slc22a7) is involved in the hepatic uptake of ketoprofen (Morita et al, 2005), and recently it has been shown that sulindac and its metabolites inhibited multiple transport proteins in primary rat and human hepatocytes as tested with model substrates, e.g., taurocholate and estradiol-17␤-glucuronide (Lee et al, 2010). To date, the molecular mechanisms of NSAID uptake into hepatocytes are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…ABCB1 is found in the canalicular surface of hepatocytes when they excrete drugs directly into the bile 15 . a previous study has reported that multiple hepatic transport proteins including aTP-binding cassette, sub-family C, member 2 (ABCC2) are inhibited by sulindac/metabolites, therefore impairing hepatic transport of bile acid by sulindac/metabolites and disturbing bile acid homeostasis, resulting in sulindac-mediated liver injury 10 . in our experiment, ABCC2 was one of the 29 differentially expressed genes between the sulindacdiclofenac group and other nSaiD groups.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional increases of these genes might reflect disturbance in hepatic transport. The expression of 'transport'-related genes might be caused by inhibition of proteins responsible for hepatic transport of drugs and/or bile acid by sulindac 10 . Both sulindac and diclofenac could regulate lipid metabolism-related genes as other hepatotoxicants.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the tested drugs exhibit high plasma protein binding; therefore, the true in vitro IC 50 values are likely to be much lower than the apparent values that were calculated. Furthermore, many drugs accumulate within hepatocytes at concentrations that are much higher than extracellular concentrations [95] and for some drugs it has been found that their metabolites (which are not produced in the membrane vesicle assay model) are more potent BSEP inhibitors than the parent compounds (e.g., troglitazone [89], sulindac [96]) and/or that BSEP inhibition requires co-expression of MRP2 (which is not present in insect cells transfected with BSEP) [32]. In addition, the fraction of transport inhibition required to cause functional alterations in bile flow in vivo that contribute to DILI progression following long-term dosing with drugs is unknown and could be much lower than the observed IC 50 values (e.g., IC 10 values).…”
Section: Bsep Inhibition Is a Human Dili Risk Factormentioning
confidence: 99%